Benzene-induced growth restriction and compensatory rebound in mouse fetuses and placentas - Megan E. Cull; Lauren T.L. Brown; Perri M. Grant; Lihua Xue; Louise M. Winn (Reproductive Toxicology, 2026)

The COSPAR international space weather action teams (ISWAT) initiative: a driving force for the COSPAR space weather roadmap - Maria M. Kuznetsova; Mario M. Bisi; Hermann J. Opgenoorth; Martin A. Reiss; M. Leila Mays; Lucilla Alfonsi; C. Nick Arge; David Barnes; Anna Belehaki; Thomas E. Berger; Amanda Brecht; Sean Bruinsma; et al. (Advances in Space Research, 2026)

Current flow in low-energy coral forereef spurs and grooves - Lachlan Perris; Tristan Salles; Thomas E. Fellowes; Ana Paula Da Silva; Stephanie Duce; Jody M. Webster; Alisha M. Thompson; Ana Vila-Concejo (Geomorphology, 2026)

Reliable identification of flood-borne deposits in speleothems using magnetic microscopy - Samuel L. Piascik; Roger R. Fu; Nicolás M. Stríkis; Ricardo I.F. Trindade; Julio Cauhy Rodrigues; Francisco W. Cruz; Gelson F. Souza-Junior; Andrea Borsato; Vitor Azevedo; Plinio Jaqueto; Isabel Tamara Pedron; Perri Thaler; et al. (Quaternary Science Reviews, 2025)

Gossypiboma-derived lethal sarcoma in a dog - A. Rigillo; G. Giulia; M. Gambini; R. Magnoni; C. Perri; S. Remoli (Journal of Comparative Pathology, 2025)

In utero benzene exposure in CD-1 mice results in increased fetal and placental size at gestational day 19, which is dependent upon intra-litter variables - Megan E. Cull; Lauren T.L. Brown; Perri M. Grant; Lihua Xue; Louise M. Winn (Reproductive Toxicology, 2025)

A case of feline intraocular neoplasm with neural crest derivation - M. Gambini; S. Bo; A. Rigillo; C. Perri; W. Marchioro; C. Giudice (Journal of Comparative Pathology, 2025)

Calorie-restriction treatment mitigates the aging in rat liver model - L. Urlandini; A. E. Leonetti; F. Conforti; A. Perri; D. Lofaro; G. Antonucci; M. Mandalà; S. Bossio; S. Di Agostino; V. Rago (Biogerontology, 2025)
The aging process promotes progressive impairment of homeostasis and the increase of the risk of disease and death. A major hallmark of the aging process is the systemic chronic inflammation which strongly contributes to the onset of aging-related diseases. In the liver, the aging condition drives the hepatocytes to develop a metabolic dysfunction-associated steatosis. Caloric restriction (CR) is a remarkable strategy to delay biological aging, occurring through several mechanisms. In this study we aimed to explore, employing an in vivo rat model, the impact of CR on aging-mediated liver inflammation markers. The experiments were performed on 14 male Sprague–Dawley rats (24 months old). At 18 months old, rats were allocated into two groups: the normal diet (ND) group was continued ad libitum diet, and the CR regimen group was fed a diet of the same chow restricted to 60% of the intake. All animals were sacrificed at 24 months old. Compared to the ND group, morphological examination of the liver revealed a lower level of fibrosis in the CR group, concomitantly with a reduced expression of key fibrotic markers, such as collagen I, fibronectin, and αSMA. Furthermore, CR improved the liver oxidative balance, as showed by the increased expression of two scavenging enzymes, SOD1/SOD. Moreover, we reported concomitant reduction of NLRP3 inflammasome signalling. Interestingly, CR significantly improved the signalling of key members of the nutrition-sensitizing affected by aging, AMPK/SIRT1/LKB1. Collectively our findings support the evidence on the metabolic benefits of CR about aging-related liver inflammation, by inducing a morphological improvement that mirrors the decrease in the expression of inflammatory molecular markers.

ELIME-IMS hybrid assay for Salmonella detection in swine mesenteric lymph nodes at slaughterhouse - M. Trevisani; M. Conter; M. Cecchini; L. Lamperti; L. Andriani; M. Rega; C. Bacci; M. Perri; S. Bonardi (Food Microbiology, 2025)

Pervasive calcite veins and cleavage dilation in low-grade metamorphic rocks as a marker of lower Jurassic rift-basin margins: A signature of microbial colonization - S. Fabbi; M. Borrelli; G. Innamorati; L. Aldega; M. Daëron; E. Perri; M. Santantonio (Marine and Petroleum Geology, 2024)

Unifying the validation of ambient solar wind models - Martin A. Reiss; Karin Muglach; Richard Mullinix; Maria M. Kuznetsova; Chiu Wiegand; Manuela Temmer; Charles N. Arge; Sergio Dasso; Shing F. Fung; José Juan González-Avilés; Siegfried Gonzi; Lan Jian; et al. (Advances in Space Research, 2023)

CME propagation through the heliosphere: Status and future of observations and model development - Manuela Temmer; Camilla Scolini; Ian G. Richardson; Stephan G. Heinemann; Evangelos Paouris; Angelos Vourlidas; Mario M. Bisi; N. Al-Haddad; T. Amerstorfer; L. Barnard; D. Burešová; S.J. Hofmeister; et al. (Advances in Space Research, 2023)

Correlations between cerebrospinal fluid biomarkers, neurocognitive tests, and resting-state electroencephalography (rsEEG) in patients with HIV-associated neurocognitive disorders - A. Barco; S. Orlando; G. Stroffolini; V. Pirriatore; A. Lazzaro; D. Vai; G. Guastamacchia; G. Noce; C. Atzori; M. Trunfio; S. Bonora; G. Di Perri; et al. (Journal of NeuroVirology, 2022)

Caterpillar survival in the city: attack rates on model lepidopteran larvae along an urban-rural gradient show no increase in predation with increasing urban intensity - Lindsay D. Nason; Perri K. Eason; Margaret M. Carreiro; Amy Cherry; Jacob Lawson (Urban Ecosystems, 2021)

Ancient DNA suggests modern wolves trace their origin to a Late Pleistocene expansion from Beringia - Liisa Loog; Olaf Thalmann; Mikkel‐Holger S. Sinding; Verena J. Schuenemann; Angela Perri; Mietje Germonpré; Herve Bocherens; Kelsey E. Witt; Jose A. Samaniego Castruita; Marcela S. Velasco; Inge K. C. Lundstrøm; Nathan Wales; et al. (Molecular Ecology, 2020)
Grey wolves ( Canis lupus ) are one of the few large terrestrial carnivores that have maintained a wide geographical distribution across the Northern Hemisphere throughout the Pleistocene and Holocene. Recent genetic studies have suggested that, despite this continuous presence, major demographic changes occurred in wolf populations between the Late Pleistocene and early Holocene, and that extant wolves trace their ancestry to a single Late Pleistocene population. Both the geographical origin of this ancestral population and how it became widespread remain unknown. Here, we used a spatially and temporally explicit modelling framework to analyse a data set of 90 modern and 45 ancient mitochondrial wolf genomes from across the Northern Hemisphere, spanning the last 50,000 years. Our results suggest that contemporary wolf populations trace their ancestry to an expansion from Beringia at the end of the Last Glacial Maximum, and that this process was most likely driven by Late Pleistocene ecological fluctuations that occurred across the Northern Hemisphere. This study provides direct ancient genetic evidence that long‐range migration has played an important role in the population history of a large carnivore, and provides insight into how wolves survived the wave of megafaunal extinctions at the end of the last glaciation. Moreover, because Late Pleistocene grey wolves were the likely source from which all modern dogs trace their origins, the demographic history described in this study has fundamental implications for understanding the geographical origin of the dog.

Females are more proactive, males are more reactive: neural basis of the gender-related speed/accuracy trade-off in visuo-motor tasks - V. Bianco; M. Berchicci; F. Quinzi; R. L. Perri; D. Spinelli; F. Di Russo (Brain Structure and Function, 2020)

Modality-specific sensory readiness for upcoming events revealed by slow cortical potentials - V. Bianco; R. L. Perri; M. Berchicci; F. Quinzi; D. Spinelli; F. Di Russo (Brain Structure and Function, 2020)

Detectable cerebrospinal fluid JCV DNA in late-presenting HIV-positive patients: beyond progressive multifocal leukoencephalopathy? - S. Mornese Pinna; E. Scarvaglieri; M. G. Milia; D. Imperiale; V. Ghisetti; S. Audagnotto; A. Prochet; F. Lipani; S. Bonora; G. Di Perri; A Calcagno (Journal of NeuroVirology, 2017)

Erratum to: Cortical reorganization in an astronaut’s brain after long-duration spaceflight - Athena Demertzi; Angelique Van Ombergen; Elena Tomilovskaya; Ben Jeurissen; Ekaterina Pechenkova; Carol Di Perri; Liudmila Litvinova; Enrico Amico; Alena Rumshiskaya; Ilya Rukavishnikov; Jan Sijbers; Valentin Sinitsyn; et al. (Brain Structure and Function, 2016)

Cortical reorganization in an astronaut’s brain after long-duration spaceflight - Athena Demertzi; Angelique Van Ombergen; Elena Tomilovskaya; Ben Jeurissen; Ekaterina Pechenkova; Carol Di Perri; Liudmila Litvinova; Enrico Amico; Alena Rumshiskaya; Ilya Rukavishnikov; Jan Sijbers; Valentin Sinitsyn; et al. (Brain Structure and Function, 2016)

Blood brain barrier impairment is associated with cerebrospinal fluid markers of neuronal damage in HIV-positive patients - A. Calcagno; C. Atzori; A. Romito; D. Vai; S. Audagnotto; M. L. Stella; C. Montrucchio; D. Imperiale; G. Di Perri; S. Bonora (Journal of NeuroVirology, 2016)

Mid-latitude coralgal bioconstruction and endolithic microbialites: environmental significance during Quaternary climate variations - M. P. Bernasconi; M. Cefalà; E. Perri (Facies, 2015)

The expanding large-spored Metschnikowia clade: Metschnikowia matae sp. nov., a yeast species with two varieties from the Brazilian Atlantic Forest - Ana Raquel de Oliveira Santos; Ami M. Perri; Maria da Graça Stupiello Andrietta; Carlos A. Rosa; Marc-André Lachance (Antonie van Leeuwenhoek, 2015)

Prevalence and predictors of blood-brain barrier damage in the HAART era - A. Calcagno; M. C. Alberione; A. Romito; D. Imperiale; V. Ghisetti; S. Audagnotto; F. Lipani; S. Raviolo; G. Di Perri; S. Bonora (Journal of NeuroVirology, 2014)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)